Wyllie's treatment of epilepsy : principles and practice. - Wyllie, Elaine.; Cascino, Gregory D.; Gidal, Barry E.; Goodkin, Howard P. (Wolters Kluwer/Lippincott Williams & Wilkins, 2011)
"In one convenient source, this book provides a broad, detailed, and cohesive overview of seizure disorders and contemporary treatment options. For this Fifth Edition, the editors have replaced or significantly revised approximately 30 to 50 percent of the chapters, and have updated all of them. Dr. Wyllie has invited three new editors: Gregory Cascino, MD, at Mayo Clinic, adult epileptologist with special expertise in neuroimaging; Barry Gidal, PharmD, RPh, at University of Wisconsin, a pharmacologist with phenomenal expertise in antiepileptic medications; and Howard Goodkin, MD, PhD, a pediatric neurologist at the University of Virginia. A fully searchable companion website will include the full text online and supplementary material such as seizure videos, additional EEG tracings, and more color illustrations"--Provided by publisher.